Impact of Artificial Intelligence on Privacy Rights - Dr.Khushbu Pareek , Dr. Santosh Sharma (South Eastern European Journal of Public Health, 2025)
Increased productivity, precision, and efficiency are just a few of the advantages that artificial intelligence (AI) technology has brought about in several industries. Yet serious worries regarding data security and privacy have been brought up by the quick development of AI. The growing dependence of AI systems on enormous volumes of personal data has raised concerns about privacy breaches and put current ethical and legal frameworks under pressure. Examining the ethical, societal, and legal ramifications of AI-driven data gathering and analysis, this study investigates how AI affects privacy rights. It emphasizes the ethical conundrums related to permission, transparency, and prejudice and points out how inadequate the current privacy rules are to handle the particular problems presented by AI technology. The study finds common themes and best practices in handling privacy problems connected to AI through in-depth case studies and content analysis. The results imply that strict permission procedures, privacy-preserving technology, and strong data protection regulations are necessary to secure people's privacy. To improve privacy protection in AI systems, the study ends with policy proposals that support open AI practices, moral standards, impartial monitoring organizations, and public awareness initiatives. In the digital era, these steps are essential for striking a balance between the advancement of AI and the defense of individual rights.